Exercise during pregnancy enhances cerebral maturation in the newborn: A randomized controlled trial. Issue 4 (21st April 2017) - Labonte-Lemoyne, Elise; Curnier, Daniel; Ellemberg, Dave
ABSTRACT: Accumulating research indicates that the regular practice of physical exercise is beneficial to the human brain. From the improvement of academic achievement in children to the prevention of Alzheimer's disease in the elderly, exercise appears beneficial across the developmental spectrum. Recent work from animal studies also indicates that a pregnant mother can transfer the benefits of exercise during gestation to her offspring's brain. Exercising pregnant rats give birth to pups that have better memory and spatial learning as well as increased synaptic density. To investigate whether this transfer from the pregnant mother to her child also occurs in humans, we conducted a randomized controlled trial ( n = 18) and measured the impact of exercise during pregnancy on the neuroelectric response of the neonatal brain with electroencephalography (EEG). Here we show that, compared to the newborns of mothers who were inactive during their pregnancy, the children of exercising pregnant women are born with more mature brains. This was measured with the infant slow positive mismatch response (SPMMR), an electroencephalographic potential known to decrease in amplitude with age. The SPMMR reflects processes associated with brain maturation via its response to sound discrimination and auditory memory. In this study, the children of the mothers who exercised throughout their pregnancy have a smaller SPMMR than the children of mothers who remained sedentary ( p = .019). Our results demonstrate the impact regular exercise during pregnancy can have on the development of the human fetal brain.